Community Integration and Social Participation for Adults with Intellectual Disabilities - Parsakia, Kamdin; Saadati, Nadereh; Rostami, Mehdi (Psychological Research in Individuals with Exceptional Needs, 2024)
The objective of this study was to explore the experiences and perceptions of community integration and social participation among adults with intellectual disabilities (ID). This qualitative research employed semi-structured interviews to gather in-depth data from 27 adults with intellectual disabilities. Participants were recruited through purposive sampling from various community centers, support groups, and social service organizations. Data were collected until theoretical saturation was achieved. Thematic analysis was used to analyze the transcribed interviews, identifying key themes and subthemes that captured the essence of the participants’ experiences and perceptions. The study identified four main themes: experiences of community integration, types of social activities, perceived benefits and challenges, and influencing factors. Participants reported a strong sense of belonging and personal growth through community activities, despite facing barriers such as stigma, accessibility issues, and financial constraints. Support systems, including family, professionals, and peer networks, played a crucial role in facilitating participation. Recreational, cultural, and educational activities, as well as volunteering, provided significant physical, emotional, and social benefits. Technological advancements, inclusive policies, and personal resilience were identified as critical factors influencing community integration. The findings highlight the importance of enhancing accessibility, support systems, and inclusive policies to promote community integration and social participation for adults with intellectual disabilities. Addressing the identified barriers and leveraging facilitators can improve their quality of life and well-being. Future research should employ mixed-methods approaches, include longitudinal studies, and consider the perspectives of family members, caregivers, and professionals to provide a more comprehensive understanding of the factors influencing community participation.